Assessing the Effectiveness of Various Chemicals against the Yellow Stem Borer in Rice - Gautam, Rajesh Kumar; Kumar, Ritesh; Chauhan, Saroj; Mourya, Pradumn Kumar (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
An experiment was conducted to assess the effectiveness of various insecticides at Heera Puri research field, IANS, DDUGU, District Gorakhpur during Kharif, 2023. Various treatments used during the period of the experiment were T1: Chlorantraniliprole 18.5 SC, T2: Emamectin benzoate 5% SC, T3: Cartap hydrochloride 50% SP, T4: Lambda-cyhalothrin 5% EC, T5: NSKE 5%, T6: Beauveria bassiana, T7: Bacillus thuringienisis T8: Control. Chlorantraniliprole 18.5 SC showed a significantly lower percentage of the dead heart followed by Emamectin benzoate 5 % SC, Lambda cyhalothrin 5% EC, Cartap hydrochloride 50% SP, NSKE, Beauveria bassiana and Bacillus thuringienisis. The highest percentage of dead hearts were found under untreated control. The significantly higher grain yield (42.45 q per ha) was obtained in Chlorantraniliprole 18.5 SC treated plots which are followed by Emamectin benzoate 5% SC (40.85 q per ha) and a higher percentage increase in yield over control was obtained (49.95 %) in Chlorantraniliprole 18.5 SC treated plots. The economics of various treatments based on net profit and cost of plant protection revealed that. the highest cost: benefit ratio Lambda cyhalothrin 5% EC (9.87) followed by Emamectin benzoate 5% SC (8.80) and Chlorantraniliprole 18.5% SC (7.70).The highest B: C ratio of Lambda-cyhalothrin 5 EC may be due to its low price and dose concentration.